2010
DOI: 10.1111/j.1420-9101.2010.02068.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐related variation in migration phenology in relation to sexual dimorphism: a test of competing hypotheses for the evolution of protandry

Abstract: Timing of arrival/emergence to the breeding grounds is under contrasting natural and sexual selection pressures. Because of differences in sex roles and physiology, the balance between these pressures on either sex may differ, leading to earlier male (protandry) or female (protogyny) arrival. We test several competing hypotheses for the evolution of protandry using migration data for 22 bird species, including for the first time several monochromatic ones where sexual selection is supposedly less intense. Acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 59 publications
4
62
0
Order By: Relevance
“…migration or molt (Morbey & Ydenberg, 2001; Kissner, Weatherhead & Francis, 2003; Saino et al, 2010; Spottiswoode & Saino, 2010). Thus, in a companion study (Saino et al, 2013) we investigated variation in timing of molt and showed that no difference in timing of molt between males and females exists for wing, tail or crown feathers.…”
Section: Introductionmentioning
confidence: 99%
“…migration or molt (Morbey & Ydenberg, 2001; Kissner, Weatherhead & Francis, 2003; Saino et al, 2010; Spottiswoode & Saino, 2010). Thus, in a companion study (Saino et al, 2013) we investigated variation in timing of molt and showed that no difference in timing of molt between males and females exists for wing, tail or crown feathers.…”
Section: Introductionmentioning
confidence: 99%
“…In dichromatic species protandry has been found to correlate with sexual dichromatism, the most dichromatic taxa showing the largest seasonal difference of passage between sexes (Rubolini et al 2004). In a larger set of species, including monochromatic ones, protandry has been found to positively covary with sexual size dimorphism but not with dichromatism, supporting a "mate choice" model with females assessing mate quality based on condition-dependent arrival date (Saino et al 2010). The earlier movements of adults with respect to yearlings observed in a number of species might be explained by the faster movements of the former, both based on more pointed wings in some species as well as experience, and on a strategy of avoidance of direct conflict upon settlement by later arriving yearlings with potentially dominating and earlier settling adults (Hill 1989, Spina et al 1994.…”
Section: Seasonality Of Movements Differential Migration Of Sex-and mentioning
confidence: 87%
“…In many bird species, males return to the breeding grounds before females (Mills 2005, Saino et al 2010, Morbey et al 2012. Such protandry is frequently attributed to competition, either for territories-the ''rank advantage hypothesis''; or for mates-the ''mate opportunity hypothesis'' .…”
Section: Introductionmentioning
confidence: 99%